Light-independent chlorophyll biosynthesis: involvement of the chloroplast gene chlL (frxC). - Suzuki, J Y (1992)
The Chlamydomonas reinhardtii chloroplast gene chlL (frxC) is shown to be involved in the light-independent conversion of protochlorophyllide to chlorophyllide. The polypeptide encoded by chlL contains a striking 53% amino acid sequence identity with the bacteriochlorophyll (bch) biosynthesis bchL gene product in the photosynthetic bacterium Rhodobacter capsulatus. In a previous analysis, we demonstrated that bchL was involved in light-independent protochlorophyllide reduction, thereby implicating chlL in light-independent protochlorophyllide reduction in photosynthetic eukaryotes. To perform a functional/mutational analysis of chlL, we utilized particle gun-mediated transformation to disrupt the structural sequence of chlL at its endogenous locus in the chloroplast genome of Chlamydomonas. Transformants for which the multicopy chloroplast genome was homoplasmic for the disrupted chlL allele exhibit a "yellow-in-the-dark" phenotype that we demonstrated to be a result of the dark accumulation of protochlorophyllide. The presence of a chlL homolog in distantly related bacteria and nonflowering land plants, which are thought to be capable of synthesizing chlorophyll in the dark, was also demonstrated by cross-hybridization analysis. In contrast, we observed no cross-hybridization of a probe of chlL to DNA samples from representative angiosperms that require light for chlorophyll synthesis, in support of our conclusion that chlL is involved in light-independent chlorophyll biosynthesis. The role of chlL in protochlorophyllide reduction as well as recent evidence that both light-independent and light-dependent protochlorophyllide reductases may be of bacterial origin are discussed.